Akuntabilitas Anggaran Covid 19 Pada Dinas Sosial Kabupaten Bima - Nurbaya, Nurbaya; Tahir, Muhammad; Harakan, Ahmad (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the accountability of the Covid 19 budget at the Bima district social service. Based on the results of the study, it showed that aspects of 1) legal responsibility and honesty, the Bima District Social Service was honest in budgeting the Covid 19 budget to the community. 2) managerially, the Bima District Social Service officially reports through the leadership to the Regent then later the Regent is executive and aka plenary in the legislature in the DPRD. 3) programs, programs implemented by the Social Service of Bima Regency, namely the empowerment program for the Poor, Remote Indigenous Communities (KAT) and People with Other Social Welfare Problems. 4) policy, the Bima District Social Service held a special division to handle the Covid 19 budget and that special division was the Social Rehabilitation and Handling of the Poor. 5) financial/financial responsibility, the Bima Regency Social Service said that the Covid 19 budget was for this and that it could not be covered up.